2019
DOI: 10.3390/toxins11110616
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of T-2 Toxin in Maize by Modified Montmorillonite Clay

Abstract: Montmorillonite clay has a wide range of applications, one of which includes the binding of mycotoxins in foods and feeds through adsorption. T-2 toxin, produced by some Fusarium, Myrothecium, and Stachybotrys species, causes dystrophy in the brain, heart, and kidney. Various formulations that include lemongrass essential oil-modified montmorillonite clay (LGEO-MMT), lemongrass powder (LGP), montmorillonite clay washed with 1 mM NaCl (Na-MMT), montmorillonite clay (MMT), and lemongrass powder mixed with montmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…e nanoformulations did not show any significant difference in the decontamination of AFG 1 in the millet samples compared with the control. However, in the previous studies, Mont-Na was proven to be the most efficient in decontaminating T-2 toxin in maize [14], while Mont-LGP was the most efficient in decontaminating zearalenone in millet [15]. Other studies have also shown that bentonite which is mainly montmorillonite is effective in the adsorption of mycotoxins, particularly aflatoxins [25,26].…”
Section: Ermogravimetric Analysis (Tga) Of the Nanoformulations From Montmorillonite Clay And Lemongrass Extractsmentioning
confidence: 98%
See 1 more Smart Citation
“…e nanoformulations did not show any significant difference in the decontamination of AFG 1 in the millet samples compared with the control. However, in the previous studies, Mont-Na was proven to be the most efficient in decontaminating T-2 toxin in maize [14], while Mont-LGP was the most efficient in decontaminating zearalenone in millet [15]. Other studies have also shown that bentonite which is mainly montmorillonite is effective in the adsorption of mycotoxins, particularly aflatoxins [25,26].…”
Section: Ermogravimetric Analysis (Tga) Of the Nanoformulations From Montmorillonite Clay And Lemongrass Extractsmentioning
confidence: 98%
“…Furthermore, a mixture of montmorillonite clay and lemongrass has been applied for the same purpose in cereal grains. Modified montmorillonite clay has proven efficient in decontaminating T-2 toxin in maize and zearalenone in millet [14,15]. e use of clay for decontamination of mycotoxins is an adsorption approach, which involves chemical and physical forces that help decrease the formation of toxins and lessen their health effects thereof in animals [16].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the reduction levels of T‐2 and HT‐2 toxins might be due to the difference in their chemical structure, and the multistep degradation that takes place during the ACP treatment (Kiš et al., 2020). The T‐2 metabolic pathway is in its rapid deacetylation at C‐4, which results in the formation of HT‐2 (Kuchenbuch et al., 2018; Monaci et al., 2011; Olopade et al., 2019), which explained the comparatively lower degradation of the HT‐2 during longer ACP treatments. Unlike mycotoxins that have long aliphatic chains, mycotoxins including T‐2 and HT‐2, that contain mixed structures of condensed rings and aliphatic chains, result in intermediate degradation (Ten Bosch et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Operations including pre-harvest control (e.g., appropriate sowing dates, balanced fertilization, pest infestation management, and selection of resistant varieties), harvest control (e.g., proper timeliness of harvest, reduction of mechanical damages, effective cleaning), and post-harvest strategies (e.g., efficient drying and good storage practices) should mitigate mycotoxin production in agricultural commodities [74]. However, it may not be possible to completely prevent the formation of T-2 in agricultural products, and decontamination strategies involving physical, chemical, and biological techniques need to be used to decontaminate T-2 toxin [75].…”
Section: T-2 Degradation and Mitigation Strategiesmentioning
confidence: 99%